ANALISIS LOKASI RAWAN KECELAKAAN LALU LINTAS DI JALAN TRANS KALIMANTAN (KUALA AMBAWANG – SIMPANG AMPAR) - Oktavianus Andri; Slamet Widodo; Siti Mayuni (JeLAST : Jurnal Teknik Kelautan , PWK , Sipil, dan Tambang, 2016)
Street Trans Borneo in the period from 2013 to 2015, there were about 72 people who died due to traffic accidents, 85 people were seriously injured, and 131 people suffered minor injuries and 167 occurrences of accidents based on data Police Pontianak. Under these conditions, the parties concerned should immediately address this to handling. Before any treatment needs to know the locations that are prone areas, it is necessary to identify the location of vulnerable stage as the first step in determining the handling of vulnerable locations or get priority handling. In connection with this, the research examined the stage of identifying the location of the accident-prone by using various parameter levels or the number of accidents that connects the variables the number of accidents in whole or accident fatal victims, the length of road, the potential of the surrounding environment (vehicles registered and the total population), volume flow vehicles, as well as the number of casualties following the severity weighting. Parameters that are used, among other things: Criteria reaction, RPBAR (population districts and counties), RDRBOR, Severity Index, TK, EPDO, EAN, RABROVT, RCS, RMVM, and Rair, then controlled by the limit values, namely: approximate value (EV), the value of the upper limit (UCL), and the critical value (CR) in order to get the order of priority of traffic accident-prone locations. Results of the analysis showed that the Trans Kalimantan has the highest severity level value at end of period (2015) is 20-25 with a value of KM 20, KM 15-20 followed by a value of 13, KM KM 5-10 and 25-30 with 12 points, KM 30-35 and 45-50 with the value of KM 5, KM 55-60 with a value of 1, and 0-5 KM, KM 10-15, 35-40 KM, KM 40-45, 50-55 KM, KM 60- 65, KM 65-70, 70-75 KM with a value of 0 is not a vulnerable location at the end of the study had no indicators of vulnerability. It gets first priority on KM 20-25, who has the highest value of severity, necessitating the handling of the prone locations. Stages on efforts to address areas vulnerable to traffic accidents do not stop at the stage of identification only, locations prone on the results of this study need to be investigated further at the data analysis stage, the election management techniques, construction, to monitoring and evaluation, according to the stages in the guidelines construction and building (Pd T-09-2004-B). Because in this research only discusses the determination of the location of the accident-prone traffic on the Trans Kalimantan while handling just in general or to provide recommendations which preceded to get treatment.   Keywords: Numbers of accidents, traffic accident-prone location